Cine y Televisión Irlandeses - 2022 - Roddy Flynn, (Estudios Irlandeses, 2023)
“Phew! What a year it’s been!” may sound like a phrase from the opening of a round robin letter, the kind someone in your given circle feels obliged to send every Christmas, as well-intentioned as it is boastful. On this occasion, however, it is a phrase that genuinely befits the historic year that 2022 represents in Irish film. For how else to characterise it but with a “Phew!”? Even if the overall level of screen production expenditure dropped significantly (to €361m) after the outlier that was the €500m spent in 2021, Irish cinema (if not Irish television) has simply never enjoyed anything like the profile it currently does. This is in no small part down to the role played by an awards ceremony which takes place 8,000 kilometres from Ireland and which, while we know it to be a profoundly imperfect yardstick of the quality of global cinema, is nonetheless a harbinger of an unprecedented era in Irish film.